Functional Molecular Silicon Compounds I Regular Oxidation States - Scheschkewitz, David (Structure and Bonding, 2014)
Guido Kickelbick Silsesquioxanes Jörg Wagler, Uwe Böhme and Edwin Kroke Higher-Coordinated Molecular Silicon Compounds Thomas Müller Silylium Ions Christoph Marschner Oligosilanes.